Exploring The Role of Internal Auditor Expertise, Internal Controls, and Whistleblowing Systems in Mitigating Fraud: Evidence from State-Owned Enterprises Listed on The IDX (2020-2023) - Zhafira, Neva; Khamisah, Nur (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to examine the effect of internal auditor financial expertise, internal control effectiveness, and whistleblowing system on the amount of fraud. The object of research is focused on state-owned companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. The sampling technique applied using the purposive sampling method was 22 companies that met the criteria. Data analysis was done with descriptive statistics and panel data regression. Based on the results of the study, it shows that partially the variables of internal auditor financial expertise and the effectiveness of internal control have no effect on the amount of fraud. However, the whistleblowing system variable has a positive effect on the amount of fraud. This indicates that the higher the financial expertise of internal auditors and the effectiveness of internal control owned by the company have no influence on the amount of fraud. Meanwhile, the more active the whistleblowing system is carried out, the higher the possibility of fraud being revealed.